The Illustration of Oceanic Data II : Vectors - Duncan, Peter; Oldson, John (The International Hydrographic Review, 2015)
The vectors most commonly considered in oceanic cartography are ocean currents, which can be represented in a variety of ways, according to the nature of the currents themselves, the manner in which these currents were observed, and the concepts which the illustrator wishes to display. Within the limits of a two-dimensional page there are the requirements of portraying the three-dimensional space in which the vectors were observed, the three-dimensional space of the vectors themselves and the dimension of time. Some solutions to this problem are provided from the literature.